Revisiting the role of trimetazidine for peripheral artery disease: a systematic review with meta-analysis - Raden Mohammad Budiarto,; Pandit Bagus Tri Saputra,; Roy Bagus Kurniawan,; Dinda Dwi Purwati,; Aiyaa Ulaa Dhiya Ul Haq,; Citrawati Dyah Kencono Ungu, (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the impact of trimetazidine on skeletal muscle function in patients suffering from peripheral artery disease. Method: The systematic review was conducted from July 20 to November 22, 2022, in line with the Preferred Reporting Items for Systematic Review and Meta-Analysis and comprised search for interventional studies on MEDLINE, ProQuest, Scopus and ScienceDirect databases using key words “peripheral artery disease” and “trimetazidine” or their synonyms. The cut-off date for the search was July 21, 2022. Clinical parameters, including Ankle-Brachial Index, Maximum Walking Distance, Maximum Walking Time and Pain Onset Time, were analysed both narratively and quantitatively whenever possible. Results: Of the 587 studies initially identified, 12(2%) were shortlisted. Of them, 2(16.7%) qualified for detailed analysis, comprising 172 patients with intermittent claudication. There was no significant difference between the examined groups' Ankle-Brachial Index values at baseline and post-intervention (p=0.83). Maximum Walking Distance improvement was significantly higher (p=0.0006) in trimetazidine group compared to control group. Maximum Walking Time MWT and Pain Onset Time were significantly different between control and trimetazidine groups (p<0.05). Conclusion: Trimetazidine's anti-ischaemic effect in peripheral artery disease patients improved Maximum Walking Distance, while it had no significant influence on Ankle-Brachial Index. Well-designed studies addressing the issue are needed. Key Words: Trimetazidine, Coronary, Ankle, Arterial disease, Muscle, Skeletal, Walking.